Peculiarities of language cliches manipulative influence on massmedia communication (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article reveals the problem of consciousness manipulation process and the role of stereotype language units in it. Language influence made upon the addressee is considered in the aspect of linguapragmatics. The research also shows pragmatics of language cliches in modern Ukrainian media. Using clishes determines the opportunity to manipulate both collective consciousness.
Keywords: massmedia discourse; language cliché; pragmatic; manipulation; manipulation influence